KUALITAS PELAYANAN PERSYARATAN IZIN MENDIRIKAN BANGUNAN (IMB) DI DINAS PENATAAN RUANG DAN PERUMAHAN KOTA PALU - Mayasari, Mayasari (Katalogis, 2016)
One role of the Department of Spatial Planning and Housing is to provide the Permits Building License Service. The granting of licenses is intendedÂ  that building activities are in accordance with its designation and spatial plan and urban areas in order to implement the content of the plan, then the need for certificates of Permits Building License, which will provide certainty and legal guarantees to the people. This research aims at knowing how the quality of service of the Department of Spatial Planning and Housing in giving permits building license service (IMB). The research method used is descriptive qualitative. Teachniques of the data collection are in-depth interviews direct observations and documentations. The theory used from Fandy Tjiptono (1995: 25) explains that the quality of service criteria are politeness and friendliness, responsibility, convenience, comfort and completeness of facilities. The conclusion is that the Department of Spatial Planning and Housing in providing Permits Building services have been good and running properly. It could be seen from the politeness and hospitality given by the employee, the ease and convenience provided in the Permits Building License arrangement at the Department of Spatial Planning and Housing, however, the completeness of the means are not sufficient, this can be seen with the lack and the destruction of operational vehicles used by the employee to get off the field.